2018
DOI: 10.2139/ssrn.3142627
|View full text |Cite
|
Sign up to set email alerts
|

Twin Deficits Revisited: A Role for Fiscal Institutions?

Abstract: We revisit the twin deficit relationship for a sample of 193 countries over the period 1980-2016, using a panel fixed effect (within-group) estimator, bias-corrected least-squares dummy variable, system GMM, and common correlated effects pooled estimation procedures. The analysis accounts also for the existence of fiscal rules in place, their features, and their interaction with the budget balance. In the absence of fiscal rules, the twin deficit hypothesis is confirmed. The size of the estimated coefficient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
2
5
0
1
Order By: Relevance
“…We further applied Granger causality test the results concluded that there is a strong inverse causal relationship between budget deficit and current account deficit meaning that Keynesian preposition is more plausible than Ricardian Equivalence theorem in the light of above data. Our results are consistent with Banday and Aneja, (2019); Banday and Aneja, (2016); Ganchev, 2010; Bhat and Sharma (2018); Badinger et al (2017), and Afonso et al (2018).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We further applied Granger causality test the results concluded that there is a strong inverse causal relationship between budget deficit and current account deficit meaning that Keynesian preposition is more plausible than Ricardian Equivalence theorem in the light of above data. Our results are consistent with Banday and Aneja, (2019); Banday and Aneja, (2016); Ganchev, 2010; Bhat and Sharma (2018); Badinger et al (2017), and Afonso et al (2018).…”
Section: Resultssupporting
confidence: 92%
“…Ricardian hypothesis is not supported. Afonso et al (2018) studied 193 countries over the period of 1980-2016 using fixed effect model and system GMM model. The results find the existence of fiscal policy reduces the effect of budget deficit on current account deficit.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…The empirical literature on the relation between the budget deficit and the external deficit presents different results regarding the existence of causality between both types of deficits and the direction of causality. Abell (1990), Rosenweig and Tallman (1993), Vamvoukas (1999), Piersanti (2000), Salvatore (2006), Beetsma et al (2008), Daly and Siddiki (2009), Forte and Magazzino (2013), Trachanas and Katrakilidis (2013) and Afonso et al, (2018) all provide empirical support for the Twin Deficit Hypothesis, i.e., that the budget deficit causes the external deficit. On the contrary, there is no causal relationship between deficits in Algieri (2013), which validates the Ricardian Equivalence Hypothesis.…”
Section: Empirical Evidencementioning
confidence: 84%
“…Naturally, this argument holds when the government budget is not fully financed by domestic private saving and needs to be financed by foreign capital inflows. However, a budget deficit can lead to an increase in the net lending position of the private sector to such an extent that there is no effect on the current account balanceor the latter may even move towards an opposite direction and turn positive, resulting in a "twin divergence" (see also Afonso et al, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As opposed to the conventional Keynesian view, the Ricardian hypothesis of Barro (1989) asserts that the budget deficit and current account deficit have no relationship. Afonso et al (2018), Enders and Lee (1990), Kim and Roubini (2008), and Müller (2008) reveal that the increase in budget deficit decreases current account deficit and accepts a “Twin Divergence” theorem. In my own study, Banday and Aneja (2017, 2019)tested the Ricardian and Keynesian preposition, the result finds there is a bidirectional causality between budget deficit and current account deficit.…”
Section: Introductionmentioning
confidence: 99%